Archaeological heritage and education: An international perspective on History Education (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This series of papers on the role of archaeology and heritage in history lessons in elementary and secondary schools is a unique volume of archaeology in history textbooks and classrooms as well as teaching and learning archaeology through museums and historical sites. Diverse in approach and scope, the book brings forth epistemologies and ontologies of teaching archaeology in elementary and secondary schools ornamented with case-studies from four continents and twelve countries. Crosscutting issues between archaeology and history particularly in translating knowledge in education and positively impacting the communities’ understanding of the significance of history and heritage in their daily lives makes this book relevant to anyone interested in how the past is taught and learned.
Keywords: Danijela Trškan; Špela Bezjak; archaeology; museums; historical sites; heritage; education